Melampaui Retribusi: Restorative Justice untuk Pemulihan Aset Negara dari Korupsi - Andi Fahrul; Nasrul Nasrul; Firmansyah Hibbu; Phireri Phireri; Herman B (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2026)
This study aims to determine and analyze the significance of the application of the concept of restorative justice in corruption cases and the model for applying the concept of restorative justice in corruption cases. This research uses a normative empirical research method with a legal and social approach. Primary and secondary data sources are used. Data analysis will be conducted using observational-sensory and theoretical-rational methods, employing a reasoning model that first utilizes inductive logic and then continues with deductive logic. The results of this study are The significance of restorative justice is its potential to recover state losses and create more substantive accountability, but it can only be applied to certain corruption cases that meet strict requirements, such as small losses and no wide impact, so as not to erode the deterrent effect and substantive justice, The retributive justice paradigm which is the legal basis for eradicating corruption is not relevant to the main objective of corruption eradication law in Indonesia. The spirit to save state assets must be based on restorative justice thinking that is oriented towards recovery from the consequences of corruption rather than focusing on imprisoning perpetrators of corruption and The concept of restorative justice in the punishment of perpetrators of corruption can be implemented in the form of strengthening the norms of returning state losses from additional punishment to the main punishment and The model for implementing the restorative justice concept in corruption cases must be supported by strong regulations and strict oversight to ensure the goal of recovering state losses is achieved without sacrificing the principle of justice. Therefore, the model for implementing restorative justice at the police level is based on Police Regulation No. 08 of 2021 concerning Handling Criminal Acts Based on Restorative Justice. Restorative justice is an effort hoped for by the public who desire reparation for losses suffered as a result of criminal acts. Public participation in resolving cases using a restorative justice approach can also increase public awareness of the law, thus also serving to prevent crime.